How robust is the R&D-productivity relationship? Evidence from OECD countries - Kul B. Luintel; Mosahid Khan; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2010)
We examine the robustness of R&D and productivity relationship in a panel of 16 OECD countries. We control for fifteen productivity determinants predicted by different theoretical models. Following the advances in non-stationary panel data econometrics, we estimate four variants of thirteen specifications. All models appear co-integrated. Results are rigorously scrutinized through extensive bootstrap simulations and sensitivity checks. R&D and human capital emerge robust in all specifications making them universal drivers of productivity across nations. Most other determinants are also significant. Productivity relationships are heterogonous across countries depending on their accumulated stocks of knowledge and human capital.
Keywords: F12; F2; O3; O4; C15; 330; R&D Capital Stocks; Multifactor Productivity; Heterogeneity; Panel Cointegration; Bootstrap Simulations; Forschungs- und Technologiepolitik; Betriebliche Forschung; Produktivität; OECD-Staaten